1991
DOI: 10.4141/cjas91-075
|View full text |Cite
|
Sign up to set email alerts
|

The effect of garlic (Allium sativum) on feed palatability of horses and feed consumption, selected performance and blood parameters in sheep and swine

Abstract: For personal use only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
2
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 2 publications
1
13
2
4
Order By: Relevance
“…The result of the blood chemistry obtained is shown in Table 2 or Figure 1.The blood chemistry revealed significant difference (P<0.05) in high-density lipoprotein (HDL), low density lipoprotein (LDL) and total cholesterol but not significantly different (P>0.05) in triglycerides (TG) levels among dietary treatments. This is at variance with the reports of Horton et al [20] and Anassori et al [21] that garlic had no effects on plasma cholesterol and triglycerides concentration in sheep. The values obtained in the study for total cholesterol; diet 1 (74.99±6.77mg/dl) (4.162mmol/l); diet 2 (65.95±5.12mg/dl) (3.66mmol/l); diet 3 (65.57±6.8mg/dl) (3.634mmol/l); diet 4 (58.29±16.96mg/dl) (3.234mmol/l) were higher than the values of cholesterol in Yankasa ram (2.5mmol/l), Ouda ram (2.5mmol/l) and Balami ram (3.5mmol/l) reported by Njidda et al; [22] but diet 5( 39.8±8.22mg/dl) (2.209mm/dl) was lower than the values reported in the literature.…”
Section: Resultscontrasting
confidence: 90%
“…The result of the blood chemistry obtained is shown in Table 2 or Figure 1.The blood chemistry revealed significant difference (P<0.05) in high-density lipoprotein (HDL), low density lipoprotein (LDL) and total cholesterol but not significantly different (P>0.05) in triglycerides (TG) levels among dietary treatments. This is at variance with the reports of Horton et al [20] and Anassori et al [21] that garlic had no effects on plasma cholesterol and triglycerides concentration in sheep. The values obtained in the study for total cholesterol; diet 1 (74.99±6.77mg/dl) (4.162mmol/l); diet 2 (65.95±5.12mg/dl) (3.66mmol/l); diet 3 (65.57±6.8mg/dl) (3.634mmol/l); diet 4 (58.29±16.96mg/dl) (3.234mmol/l) were higher than the values of cholesterol in Yankasa ram (2.5mmol/l), Ouda ram (2.5mmol/l) and Balami ram (3.5mmol/l) reported by Njidda et al; [22] but diet 5( 39.8±8.22mg/dl) (2.209mm/dl) was lower than the values reported in the literature.…”
Section: Resultscontrasting
confidence: 90%
“…In the current study, no difference was observed in T‐CHO, HDL‐CHO, LDL, and NEFA, indicating that GP up to 0.5% of concentrate has no effect on lipid metabolism in rams. These results are in agreement with the findings reported by Horton et al , who demonstrated that GP supplementation had no influence on plasma cholesterol and triglyceride levels in sheep and swine. Obviously, no changes in the protein of blood, including total protein and albumin, were observed, indicating that GP up to 0.5% of concentrate is not sufficient to alter the protein indices of blood.…”
Section: Discussionsupporting
confidence: 94%
“…Horton et al. () reported that garlic had no effects on plasma cholesterol and triglyceride concentrations. Lau et al.…”
Section: Discussionmentioning
confidence: 99%